Eksplorasi Coro Lemah (Nauphoeta Cinerea): Studi Etnozoologi Dalam Praktik Pengobatan Tradisional di Masyarakat Desa Jepat Lor - Muizzatul Mila; Fadly Husain (Universitas Lambung Mangkurat, 2025)
Indonesia is a country with the nickname mega biodiversity with its biodiversity. The stone cockroach (nauphoeta cinerea) in Jepat lor Village community is called coro lemah, which is one of the insects that has various potentials, especially in the field of traditional medicine. However, the knowledge of the utilization of coro lemah is not widely known by the community. This study aims to document the local knowledge of the Jepat lor Village community in the utilization and public perception of traditional treatment of toothache using coro lemah. Data were collected through interviews with selected informants such as stone cockroach healers, toothache patients, and the local community. Qualitative descriptive data were collected by means of observation, interviews, and documentation. Data analysis was carried out in three stages: data reduction, presentation, and conclusion drawing. The results of the study show that the treatment practice is carried out by a healer called ‘Pak Yik’ with three stages, namely finding the weak coro lemah, sequencing, and polishing. People's perspectives on treatment depend on experience and knowledge. People who have had treatment with coro lemah have a positive view and even recommend the treatment to their closest people. While people who have not tried, have varied responses ranging from fear, amused, to enthusiasm. knowledge about treatment practices fosters community interest in exploring the potential of coro lemah.